2022
DOI: 10.3389/fpls.2022.1012923
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and selection of downy mildew resistance in spinach cv. whale by low coverage whole genome sequencing

Abstract: Spinach (Spinacia oleracea) is a popular leafy vegetable crop and commercial production is centered in California and Arizona in the US. The oomycete Peronospora effusa causes the most important disease in spinach, downy mildew. A total of nineteen races of P. effusa are known, with more than 15 documented in the last three decades, and the regular emergence of new races is continually overcoming the genetic resistance to the pathogen. This study aimed to finely map the downy mildew resistance locus RPF3 in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…For the Viroflay x Lazio panel, 192 seedlings (comprising 142 resistant and 48 susceptible seedlings and two parents) were sequenced to generate genotype datasets. In addition, 192 progeny panels segregating from Viroflay x Whale for race 5 of P. effusa reported earlier [ 16 ] were included to perform a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the Viroflay x Lazio panel, 192 seedlings (comprising 142 resistant and 48 susceptible seedlings and two parents) were sequenced to generate genotype datasets. In addition, 192 progeny panels segregating from Viroflay x Whale for race 5 of P. effusa reported earlier [ 16 ] were included to perform a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Downy mildew pathogen resistance from field evaluations in the diverse germplasm panel showed R genes between 0.3 to 1.5 Mb of chromosome 3 in Monoe-Viroflay genome assembly [ 15 ]. The RPF3 locus in Whale was located at 1.25 Mb and at 2.73–2.74 Mb in Monoe-Viroflay genome assembly, and three regions of Sp75 genome assembly located at 1.19, 1.22–1.23, and 1.75–1.76 Mb [ 16 ]. The RPF2 locus was recently reported to be between 1.11 to 1.72 Mb on chromosome 3 of Sp75 genome assembly [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, one region was identified at 0.5–1.5 Mb of the S. oleracea chromosome 1 (Fig. 5c), overlapping with the downy mildew (DM) resistance loci, RPF1 – RPF3 (Bhattarai et al, 2022; Gao et al, 2022; She et al, 2018), RPF11 (Dijkstra and Raedts, 2019), and RPF12 (Dijkstra and Raedts, 2019), which confer resistance against at least 17 downy mildew of the 19 races of this pathogen reported in spinach. A neighbor-joining tree using SVs within this introgression region relationship in the 94 Spinacia accessions suggested that the DM loci originated from both wild species as donors (Fig.…”
Section: Main Textmentioning
confidence: 97%